Sejarah Dan Dinamika Pembangunan Nagari Ambuang Kapua: Tinjauan Kearifan Lokal Dan Potensi Wilayah Otonom - Nurfarhanah; Marisa Revalina; Aisyah Putri; Mely Zamri; Nafisha Azdra Sahira; Afif Abdulhadi (CV. ITTC INDONESIA, 2026)
A dynamics have not been formally documented in written form, posing a risk of distorting the collective memory of the younger generation. This article aims to document the history of the formation of Nagari Ambuang Kapua, analyze the underlying factors behind the lack of historical documentation, and map its potential as an autonomous region. The research method utilized is descriptive qualitative, with data collection techniques consisting of in-depth interviews, observation, and document analysis. The results indicate that the naming and formation of the region were grounded in the principle of